2001
DOI: 10.1046/j.1464-5491.2001.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Near‐normoglycaemic remission in African‐Americans with Type 2 diabetes mellitus is associated with recovery of beta cell function

Abstract: Forty-two per cent of newly diagnosed, unselected African-Americans with Type 2 diabetes, treated intensively using pharmacological agents, education and diet developed near-normoglycaemic remission. Remission was associated with a greater recovery of glucose-stimulated insulin secretion suggesting that therapies directed at promoting beta cell recovery and preservation are potentially useful approaches to the treatment of Type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 27 publications
5
69
0
3
Order By: Relevance
“…Indeed, after the initial episode of acute insulin deficiency, these patients restore their insulin secretion for a long period of time, helping them to develop normoglycemic remissions lasting for up to 10 years. This pattern of acute and reversible insulin deficiency has already been described by other investigators (6,25). We show that the evolution of ␤-cell dysfunction in non-insulin-dependent ketosis-prone type 2 diabetes is slowly progressive and more similar to that of type 2 diabetes than to that of type 1 diabetes: 10 years after diabetes onset, patients with non-insulin-dependent ketosis-prone type 2 diabetes have lost only 60% of their insulin secretory capacity relative to nonobese control subjects (compared with 61% in type 2 diabetes), and 40% of these patients are still non-insulin dependent (compared with 32.5% in type 2 diabetes).…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, after the initial episode of acute insulin deficiency, these patients restore their insulin secretion for a long period of time, helping them to develop normoglycemic remissions lasting for up to 10 years. This pattern of acute and reversible insulin deficiency has already been described by other investigators (6,25). We show that the evolution of ␤-cell dysfunction in non-insulin-dependent ketosis-prone type 2 diabetes is slowly progressive and more similar to that of type 2 diabetes than to that of type 1 diabetes: 10 years after diabetes onset, patients with non-insulin-dependent ketosis-prone type 2 diabetes have lost only 60% of their insulin secretory capacity relative to nonobese control subjects (compared with 61% in type 2 diabetes), and 40% of these patients are still non-insulin dependent (compared with 32.5% in type 2 diabetes).…”
Section: Discussionsupporting
confidence: 77%
“…However, the ability of lifestyle changes to promote β-cell 'recovery' is not universal. By introducing lifestyle changes, including alterations in nutrient content to reduce carbohydrate consumption among patients, McFarlane et al 7 found that roughly half achieved a complete remission of T2D, including a normalisation of β-cell function. Despite a lack of complete functional restoration of β-cells, the remaining patients experienced improvements in insulin sensitivity with reduced reliance on pharmacological therapies.…”
Section: Discussionmentioning
confidence: 99%
“…5 Indeed, these results are sufficiently effective that many scientists and physicians promote such a dietary change as a 'first approach' to managing diabetes. 5 Such a perspective is based on evidence indicating reduced or complete cessation of insulin therapy, 6 as well as improved β-cell function, 7,8 in response to dietary intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors have described this subcategory in other ethnic groups, such as Native Americans and Hispanic Americans (5). The initial manifestation of the diabetes in these cases may be ketoacidosis similar to type 1A diabetes, although the course of the disease is unusual as insulin therapy is initially needed to maintain metabolic control and, after a variable period of time (usually within months), good control can be achieved with either diet or oral agents (5)(6)(7)(8)(9). On the other hand, these patients differ from those with type 1A diabetes because their physical characteristics are more typical of patients with type 2 diabetes; they are often obese or overweight at the time of diagnosis and, in most of the cases, there is a family history of type 2 diabetes (5).…”
mentioning
confidence: 99%